Pengaruh Sistem Raward dan Lingkungan Kerja Terhadap Kinerja Karyawan di PT Pertamina (PERSERO) Jakarta Pusat - Cahyaningsih, Amalia Nur; Indriyani, Furi; Napitupulu, Rohani Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
PT Pertamina (Persero) is one of the largest state-owned enterprises (BUMN) in Indonesia and plays an important role in supporting national energy security. The aim of this study is to determine the influence of the reward system and work environment on employee performance at PT Pertamina (Persero) in Central Jakarta. A quantitative method with a statistical approach was used. A sample of 100 permanent employees was selected using purposive sampling based on the following criteria: age between 22 and 55 years, minimum education level of high school or equivalent, and minimum work period of one year. The independent variables in this study are the reward system and the work environment, and the dependent variable is employee performance. The results showed that the reward system has a positive and significant partial effect on employee performance, with a calculated t-value greater than the t-table value (2.988 > 1.984) and a significance level of 0.004 < 0.05. The work environment also positively and significantly affects employee performance, with a calculated t-value greater than the critical value (5.291 > 1.984) and a significance level of 0.000 < 0.05. Additionally, both independent variables had a positive and significant effect on employee performance, with a calculated F-value of 73.801 > F-table of 3.090 and a sig-level of 0.000 < 0.05.